Hypoxic Preconditioning Attenuates Reoxygenation-Induced Skeletal Muscle Dysfunction in Aged Pulmonary TNF-α Overexpressing Mice - Chuang, Chia-Chen; Zhou, Tingyang; Olfert, I. Mark; Zuo, Li (Frontiers in Physiology, 2018)
Aim. Skeletal muscle subjected to hypoxia followed by reoxygenation is susceptible to injury and subsequent muscle function decline. This phenomenon can be observed in the diaphragm during strenuous exercise or in pulmonary diseases such as chronic obstructive pulmonary diseases (COPD). Previous studies have shown that PO2 cycling or hypoxic preconditioning (HPC), as it can also be referred to as, protects muscle function via mechanisms involving reactive oxygen species (ROS). However, this HPC protection has not been fully elucidated in pulmonary TNF- overexpressing (Tg+) mice (a COPD-like model). We hypothesize that HPC can exert protection on the diaphragms of Tg+ mice through pathways involving ROS-PI3K-Akt-ERK, as well as the mitochondrial ATP-sensitive potassium channel (mitoKATP) and permeability transition pore (mPTP). Methods. Isolated Tg+ diaphragm muscle strips were either non-treated, or treated with HPC, incubated with signaling cascade inhibitors, or incubated with mitochondrial channel enhancers/blockers， followed by 30-min hypoxia and 15-min reoxygenation periods. Data were analyzed by multi-way ANOVA and expressed as means ± SE. Results. Muscle treated with HPC showed improved muscle function during reoxygenation (n = 5, p < 0.05). Inhibition of ROS, PI3K, Akt, ERK, as well as mitochondrial mediators, abolished the protective effect of HPC. Individual regulation of mitochondrial channels with either the opening of mitoKATP channel or the closure of mPTP alleviated muscle function decline, suggesting that mitochondria play a role in HPC initiation (n = 5; p < 0.05). Conclusion. HPC may protect respiratory skeletal muscle function in Tg+ mice during reoxygenation through cell signaling cascades and regulations of mitochondrial channels.